‘It is well with the child’: Changing Views on Protestant Missionary Children's Health, 1870s–1930s - Morrison, Hugh Douglas (Studies in church history, 2022)
Esme Cleall observes that for nineteenth-century British missionary families ill-health was constructed as being ‘reflexive of and contributory to a specifically missionary identity’. This article argues that while this was a persistent theme, a new and significantly different discourse emerged emphasizing missionary families’ health. Children were central to this discursive shift. The article focuses on missionary children's health, using selected Anglo-American cases. There was an uneasy overlap of religiously motivated rhetoric that still expected illness and death to be part of missionary childhood experience, and a professionalized discourse that redefined missionary families as sites of health and well-being. This culminated in medical and academic literature within religious and missionary circles that constructed missionaries’ children as a new category. Thus churches responded both to the development of the medical profession and to the development of modern child-centred thinking and practices, in the process developing a new missiological or theological response to childhood.